Efficacy and safety of ‘dropless vitrectomy surgery’ and comparison of outcomes to standard of care topical therapy - Chalam, K. V.; Ahmed, Harris (Frontiers in Ophthalmology, 2023)
Objective/Background: To compare the effectiveness of intravitreal injection of triamcinolone acetonide/moxifloxacin (Tri-Moxi) with the standard eye drop regimen for controlling postoperative inflammation, intraocular pressure, infections, macular thickness, and visual acuity (VA) in patients undergoing pars plana vitrectomy for various retinal disorders. Subject/Methods: In this retrospective longitudinal study, patients who underwent vitrectomy using intravitreal Tri-Moxi at the end of surgery (Group 1) were compared with those who received standard topical steroid antibiotics (Group 2) in terms of intraocular inflammation, intraocular pressure, macular thickness based on optical coherence tomography, and visual acuity. Results: In total, 162 consecutive eyes (group 1 [81 eyes]; group 2 [82 eyes]) were included. VA improved by two lines in both groups at 90 days. In Group 1, preoperative VA (logMAR) was 0.92 (0.66) compared to 0.92 (0.75) in Group 2 (p = 1), while at 3 months, it was 0.61 (0.3) and 0.57 (0.3), respectively (p = 0.46). Group 1 showed superior outcomes concerning central foveal thickness. The average central foveal thickness CFT ( µm) in group 2 preoperatively was 423 (95) and 348 (63) at 3 months compared to group 1 526 (109) and 306 (108) preoperatively and 3 months, respectively (p = 0.042). There was no statistically significant difference in the rate of elevated intraocular pressure between the two groups or anterior chamber cell reaction severity, and no cases of endophthalmitis were observed in either group. Conclusions: Tri-Moxi is effective after vitrectomy and is not inferior to standard postoperative topical therapy.